Behavioural Flexibility and Personality in Zebra Finches. (28th April 2013) - Brust, Vera; Wuerz, Yvonne; Krüger, Oliver; Wright, J.
Abstract Consistent individual differences in behaviour of animals, that is, personalities, are both widespread and widely studied, but very few studies also include cognitive traits in this context. Animal personality has recently been integrated into the pace‐of‐life‐syndrome hypothesis, relating individual behavioural traits to life history. Variation in cognitive traits could be explained well by this theoretical framework. A risk‐reward trade‐off might lead to different cognitive types: Active birds that learn fast, take risks and probably have a fast lifestyle and less active, slow learning birds that are risk averse but thereby perform better in reversal learning as they probably pay more attention to external cues. We investigated the performance of zebra finches (Taeniopygia guttata) in a cognitively challenging reversal learning task and linked this to two personality traits: activity and fearfulness. Male birds were better in reversal learning than females. While no personality‐related differences occurred in the initial learning of our task, more active and fearful birds relearned the cue–reward association faster. While birds of different sex might have revealed different risk‐taking strategies in the training, our findings do not reveal the expected direction of a risk‐reward trade‐off in the reversal learning. It seems likely that a more general and personality‐related cognitive ability might improve performance across different tasks. The linkage between personality and cognition documented here could hence suggest that cognitive traits are indeed part of an overall pace‐of‐life syndrome.